2008
DOI: 10.2174/156652408784533760
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Mechanisms of Stress-Induced Intestina Damage

Abstract: Stress has been shown to have both central and peripheral effects, promoting psychological illness (such as anxiety and depression), as well influencing peripheral disease in the intestine. Stress in humans can exacerbate symptoms of irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD), lowering visceral pain thresholds and decreasing mucosal barrier function. Studies in rodents have revealed that both acute and chronic exposure to stressors can lead to pathophysiology of the small and large int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
164
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(175 citation statements)
references
References 75 publications
(150 reference statements)
2
164
0
9
Order By: Relevance
“…Other studies performed in male rats indicate an alteration of the intestinal barrier at weaning in the maternal separation model 23 that was detected by the significant increase of colonic short-circuit current and horseradish peroxidase flux along with increased intestinal permeability that was still maintained in adulthood. 6,34 Glucocorticoids play a role in the increased intestinal permeability induced by a short acute maternal separation stress in PND10 pups 17 but not in adult rats subjected to repeated maternal separation. 36,37 In the present study, we found no correlation between corticosterone plasma levels and intestinal permeability at weaning, either in LNS or BMS models, suggesting that glucocorticoids are not involved in the mechanisms contributing to the altered permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies performed in male rats indicate an alteration of the intestinal barrier at weaning in the maternal separation model 23 that was detected by the significant increase of colonic short-circuit current and horseradish peroxidase flux along with increased intestinal permeability that was still maintained in adulthood. 6,34 Glucocorticoids play a role in the increased intestinal permeability induced by a short acute maternal separation stress in PND10 pups 17 but not in adult rats subjected to repeated maternal separation. 36,37 In the present study, we found no correlation between corticosterone plasma levels and intestinal permeability at weaning, either in LNS or BMS models, suggesting that glucocorticoids are not involved in the mechanisms contributing to the altered permeability.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In preclinical studies, rodents raised under conditions of intermittent maternal separation develop features of IBS-like manifestations and alterations in behavior when they are adults. [3][4][5][6] Another model of early-life adverse events is the rearing of pups by dams subjected postpartum to conditions of limited bedding and nesting stress. 7,8 This model has face validity in humans 7,8 where the mother is continuously present but provides an altered repertoire of maternal behaviors indicative of fragmented and erratic care 9 and altered dam-pup interactions.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Animal studies also found that early life stressful events such as MS in the rodent can cause disruption of the HPA axis. 7,25,26 Early life stress can influence development of the HPA axis, as well as regulation of satiety-related hormones, leptin, insulin, and ghrelin, again influencing appetite, feeding behavior, and metabolism, which results in the development of obesity. 27 The weight of MS rats can gradually return to normal level on PND56, suggesting that the harmful effect of MS on weight can be improved in rat adulthood after normal feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines and the vagal system in turn can modulate the activity of the CNS and ENS. 38,39 Furthermore, increased permeability of the gut can also increase the translocation of metabolic products such as lipopolysaccharide (LPS) or neuroactive peptides created by the bacteria that can alter the activity of the ENS and CNS. 40 For example, LPS can activate Toll-Like receptors that are present on epithelial cells, enteric neurons, sensory afferent neurons in the spine, and various cells in the brain, modulating their activity and affecting the function of both ENS and CNS.…”
Section: Effect Of Gut Microbiota On Intestinal Permeabilitymentioning
confidence: 99%